How did refugees and migrants’ solidarity initiatives become an intervention for disaster and humanitarian response during the COVID-19 pandemic in Cape Town, South Africa? - Sebakwiye, Celse; Bidandi, Fred (Frontiers in Political Science, 2024)
The impact of COVID-19 on refugees and migrants in South Africa has been profound and multifaceted. Refugees, are vulnerable due to displacement, have faced a series of challenges exacerbated by the pandemic. These challenges include health risks, limited health care access, economic hardships, food insecurity, disruptions in education, mental health concerns, stigmatization, and xenophobia. The pandemic disrupted asylum procedures and hindered the delivery of humanitarian assistance. While there were efforts to address these issues, the situation remained complex and evolving, underscoring the need for targeted support and policies to protect and assist this vulnerable population during and after the pandemic. Refugees and migrant communities are in most cases the vulnerable group in times of disaster and humanitarian response. Additionally, when it comes to new arrivals or immigrant groups perceived as poorly integrated or as rivalling locals for limited resources, declining public support might occasionally limit the scope for robust humanitarian protection measures. To minimise the economic impact of the COVID-19 pandemic, South African government implemented a financial stimulus package that supported complimentary monitory measures for the citizens. This article theorises how existing structure of solidarity scholarship purposefully incorporates both the necessity of tangible response to people's needs and alternative conceptions of participation and self-organisation. This study utilized a qualitative approach, collecting data from selected migrant and refugee communities in urban centres of Cape Town, including participant from Bellville CBD, Parow Centre, Good wood Centre, and Cape Town CBD, who provided humanitarian support during the pandemic. In total seven interviews were carried out and participants were selected depending on their availability using the combination of purposive and snowball sampling techniques. Data were analysed thematically based on the research question. The study drew on pragmatic realities of refugees and migrants' solidarity initiatives and explored how they contributed to the COVID-19 humanitarian response in Cape Town, South Africa. This research aims to investigate how solidarity initiatives led by refugees and migrants have functioned as interventions for disaster and humanitarian response in the context of the COVID-19 pandemic in Cape Town, South Africa.